2024
DOI: 10.1186/s12887-024-04623-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and scores for prediction of coronary artery aneurysms in Kawasaki disease: a European monocentric study

Adriano La Vecchia,
Rita Stracquadaino,
Lucia Mauri
et al.

Abstract: Background Japanese Kawasaki disease (KD) risk scores cannot be adopted in non-Japanese patients. In North American populations a baseline coronary artery Z-score > 2 and the Son score are associated with coronary artery aneurysms (CAAs) at 4 and 8 weeks from disease onset. In European populations, the Kawanet and Kawanet-echo scores are associated with intravenous immunoglobulin resistance. This study aims to evaluate the association between KD risk scores and baseline coronary artery Z-sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…About 10–20% of patients with KD are nonresponsive to IVIGs, requiring secondary treatments, and may display an increased risk of CVAs: their early identification is critical to reinforce the standard initial approach to such patients, but all available scoring systems are unsuitable in non-Japanese populations [ 15 ]. We previously found that higher CRP values and younger age at KD onset were associated, respectively, with a failure in IVIG response and a higher risk of CVAs [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…About 10–20% of patients with KD are nonresponsive to IVIGs, requiring secondary treatments, and may display an increased risk of CVAs: their early identification is critical to reinforce the standard initial approach to such patients, but all available scoring systems are unsuitable in non-Japanese populations [ 15 ]. We previously found that higher CRP values and younger age at KD onset were associated, respectively, with a failure in IVIG response and a higher risk of CVAs [ 16 ].…”
Section: Discussionmentioning
confidence: 99%